A Surplus Production Model Considering Movements between Two Areas using Spatiotemporal Differences in CPUE: Application to Sea Ravens Hemitripterus villosus off Fukushima as a Practical Marine Protected Area after the Nuclear Accident. Issue 1 (17th August 2015) - Shibata, Yasutoki; Yamada, Manabu; Wada, Toshihiro; Itou, Masaki; Yamada, Harumi; Sohtome, Tadahiro; Iwasaki, Takashi; Sakuma, Tooru; Mizuno, Takuji
Abstract: Although the number of marine protected areas (MPAs) for stock management has increased, movements or differences in population structure of a target species between an MPA and surrounding fishing areas have rarely been considered in stock biomass estimations. We developed a surplus production model considering seasonal movements between two areas; the model was applied to Sea Ravens Hemitripterus villosus off Fukushima, where almost all fishing has been prohibited since the 2011 accident at the Fukushima Dai‐ichi Nuclear Power Plant. We predicted future biomass by using CPUE data from coastal gill‐net fishing and offshore bottom trawl fishing in 2000 to 2009. The model reflected the seasonal coastal–offshore movements of Sea Ravens well, and it predicted increasing Sea Raven biomass in both areas, which was validated by the CPUEs observed after 2010—including those for trial bottom trawl fishing that occurred within limited offshore areas after the accident. Our results indicate that the newly developed model incorporating seasonal movements of Sea Ravens is feasible and that the waters off Fukushima have effectively been serving as an MPA since the nuclear accident. We also demonstrated the model's applicability for estimating the optimal fishing effort and designing a new MPA for stock management that considers seasonal movements. Received August 29, 2014; accepted May 4, 2015